GIS-BASED DISTRIBUTION AND POPULATION ESTIMATION OF PUNJAB URIAL (OVIS VIGNEI PUNJABIENSIS) IN PAKISTAN - S. Suleman; W. A. Khan; K. M. Anjum; W. Shehzad; S. G. M. Hashmi (Journal of Animal and Plant Sciences, 2021)
The present work is the first of its kind being reported from Pakistan which was aimed to establish GIS-based distribution and population estimation of Punjab Urial (Ovis Vignei Punjabiensis) throughout its geographical range viz. Salt Range (Chakwal, Jehlum, Khushab, Kohat and Mianwali districts) and Kala Chitta Range (Attock district). Geographical coordinates were used to develop the distribution maps. Line transects and point count methods were used to estimate the population. Spatial analyst tool (Proximity) in ArcGIS software was used to demarcate the distribution area. A total of 3484 individuals of Punjab Urial were observed in the study area (7953 Km2) with a population density of 0.4 animals/Km2. A statistically significant difference (P≤0.05) was observed between both the Salt Range and Kala Chitta Range. District-wise results for population distribution revealed significantly (P≤0.05) higher number of animals observed in Mianwali district of Salt Range with a population density of 2.4 animals/Km2 while the lowest numbers of animals were observed in Attock district of Kala Chitta Range with a population density of 0.08 animals/Km2. In a nutshell, presently, the Salt Range is the main habitat for Punjab Urial in Pakistan and harbors the maximum number of animals. Furthermore, keeping in view the results on the population density of the present study it can be deduced that the habitat of Punjab Urial is gradually shrinking to Salt Range only.
Keywords: Punjab Urial; Ovis vignei punjabiensis; Population estimation; Global Positioning System